Estudio de tres tipos de trampas con el uso de dos insecticidas para el monitoreo del gusano blanco (premnotrypes vorax) en la localidad de Cuturiví Chico – Cotopaxi – Pujilí, 2022-2023. - Constante Cruz, Cristopher Joel (2023)
This research aims to provide information on the population incidence of the white potato worm (Premnotrypes vorax) in the Cuturiví Chico community, La Matriz parish located in Pujilí canton, Cotopaxi province, 13 km south of the cantonal capital by the use of innovative pest control alternatives using traps (drop traps, cover traps, and INIA traps). Its objective was to evaluate two insecticides in three types of traps for monitoring the white worm (Premnotrypes vorax). An A*B factorial arrangement was applied in a completely randomized block experimental design (DBCA) with six repetitions. The most efficient trap model is the cover one with an average of 1.30 individuals for the population presence of the potato white worm, and the best product is the one of biological origin with its active ingredient Beauveria bassiana with an average of 1.34 individuals and the best insecticide*trap interaction is the one of biological origin with its active ingredient Beauveria bassiana and the cover trap with a percentage of 1.41 individuals. In Cuturiví Chico, the white worm (Premnotrypes vorax) is present in the emergency and sprouting phase of the potato crop (Solanum tuberosum); the most efficient trap that hosted the insect was the covered trap with an average of 1.30 individuals. The research determined that the most efficient product for controlling the potato white worm (Premnotrypes vorax) is the biological insecticide with the commercial name Baukill and its active ingredient Beauveria bassiana.